Diagnosis on the implementation of the New Urban Agenda - Jose Manuel Diaz-Sarachaga; Joana Longo Sarachaga (Global Sustainability)
Abstract Non-technical summary Rapid population growth in urban areas requires an effective transposition of sustainable development goals to the urban realm, for which the New Urban Agenda was adopted by most countries worldwide. The progress report of its implementation was discussed in this study to identify strengths and weaknesses in the process that assist nations in the design and application of effective actions to achieve a more sustainable urban development.